The socio-psychological dimension of ethnic relations in Malaysia. - Ismail, Sri Rahayu; Abdullah, Haslinda; Ahmad, Zaid (eurojournals, 2009)
This article discusses the socio-psychological dimension of ethnic relations in Malaysia. It argues that in the contest of Malaysia, the psychological elements in most cases translated into negative perceptions towards others. It manifests in the forms of prejudice, stereotypes and discrimination that are seen as the most difficult stumbling block. It is crucial to understand those elements in order to understand the issue better. This paper will also highlight some of the good as well as the sour experiences that the Malaysians have gone through in dealing with the issues of ethnic relation. Meanwhile, a few strategies towards racial integration were suggested such as cultural tolerance, religious tolerance and dialogue.